Functional Characterization of parla and parlb Paralogs in Zebrafish - Merhi, Rawan (Université d'Ottawa / University of Ottawa, 2021)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease, featuring motor signs such as tremors, bradykinesia, and impaired gait that are often preceded by nonmotor symptoms such as anxiety/depression and olfactory dysfunction. Interestingly, significant olfactory loss was found to be manifested in the majority of PD patients and may precede motor symptoms by years, and thus can be used for the risk assessment of developing PD in asymptomatic individuals. The main pathological feature of PD is the progressive and irreversible loss of dopaminergic (DA) neurons in the substantia nigra pars compacta of the midbrain. Although the detailed etiology of PD remains unclear, most PD cases were found to be sporadic and can be associated with environmental factors. Only 5–10% of patients result from familial PD. With considerable effort in the past two decades, a number of genes associated with familial PD have been identified and interestingly, many of these genes are involved in regulating and maintaining mitochondrial function. The presenilin-associated rhomboid-like (PARL) gene was found to contribute to mitochondrial morphology and function and was linked to familial Parkinson’s disease (PD). The PARL gene product is a mitochondrial intramembrane cleaving protease that acts on a number of mitochondrial proteins involved in mitochondrial morphology, apoptosis, and mitophagy. To date, functional and genetic studies of PARL have been mainly performed in mammals. However, little is known about PARL function and its role in dopaminergic (DA) neuron development in vertebrates. The zebrafish genome comprises two PARL paralogs: parla and parlb. Here, we show novel information concerning the role of PARL in zebrafish by establishing a loss-of-function mutation in parla and parlb via CRISPR/Cas9- mediated mutagenesis. We examined DA neuron numbers in the adult brain and expression of genes associated with DA neuron function in larvae and adults. We show that loss of parla function, as well as loss of both parla and parlb function result in loss of DA neurons in the olfactory bulb and telencephalon of adult zebrafish brain. Changes in the levels of tyrosine hydroxylase transcripts supported this neuronal loss. Expression of fis1, a gene involved in mitochondrial fission, was increased in parla mutants and in fish with loss of parla and parlb function. Furthermore, we showed that loss of parla and/or parlb function translates into altered locomotion parameters and that loss of parla but not parlb function results in impaired olfaction. Finally, increased susceptibility to neurotoxin exposure was identified in mutants with loss of both parla and parlb function but not with loss of parla or parlb function. These results suggest an evident role for parla in the development and/or maintenance of DA neuron function in zebrafish and confirm the existence of redundant and non-redundant functions for the two paralogs, parla and parlb.
Keywords: zebrafish; parla and parlb; parkinson's disease; dopaminergic neurons; CRISPR/Cas9